Bibliometric Study of Microwave-Assisted Synthesis of Flavanone Derivatives - Poerwono, Hadi; Rudyanto, Marcellino (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to describe various studies related to synthesizing flavanone derivatives using the microwave-assisted method with a bibliometric approach. Metadata information was collected from Scopus on June 30th, 2023, with three keywords (microwave-assisted OR microwave, synthesis, and flavanone) searched for article titles, abstracts, and keywords. Analysis and research mapping were carried out with VOSviewer. Of the 33 articles relevant for analysis, 15 keyword clusters were obtained, most of which contained a list of flavanone derivatives. Interestingly, none of these clusters contain keywords for well-known compounds from the flavanone group, such as pinostrobin, pinocembrin, or hesperetin. In other words, there is an excellent opportunity to obtain novelty for microwave-assisted derivatization studies of flavanones. The chances of publication of these studies are greater in Chemistry of Heterocyclic Compounds (Springer Nature), Oriental Journal of Chemistry (Scientific Publishers), and Tetrahedron Letters (Elsevier), each with three documents. Meanwhile, most researchers on this topic come from India with 13 documents. This information allows researchers on this topic to determine potential flavanones that have the opportunity to be derivatized by the microwave-assisted method.